Prefrontal Cortex 2018
DOI: 10.5772/intechopen.79255
|View full text |Cite
|
Sign up to set email alerts
|

Prefrontal Cortex: Role in Language Communication during Social Interaction

Abstract: One important question that remains open for the relationship between the brain and social behavior is whether and how prefrontal mechanisms responsible for social cognitive processes take place in language communication. Conventional studies have highlighted the role of inferior frontal gyrus (IFG) in processing context-independent linguistic information in speech and discourse. However, it is unclear how the medial prefrontal cortex (mPFC), the lateral prefrontal cortex (lPFC), and other structures (such as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 97 publications
1
5
0
Order By: Relevance
“…Inference: That person is poor). The extent to which an inference is engaged can be systematically involved in the medial prefrontal cortex [33], a region critical to decoding nonverbal meaning in social communication [34]. Consistent with previous literature, our data shows the social expressions that mark pragmatic functions were modulated by fantasy; moreover, the more imaginative to the cartoon animals, the more expressive the stickers were perceived [34].…”
Section: Individual Characteristics and Evaluation Of Animal Stickerssupporting
confidence: 88%
See 1 more Smart Citation
“…Inference: That person is poor). The extent to which an inference is engaged can be systematically involved in the medial prefrontal cortex [33], a region critical to decoding nonverbal meaning in social communication [34]. Consistent with previous literature, our data shows the social expressions that mark pragmatic functions were modulated by fantasy; moreover, the more imaginative to the cartoon animals, the more expressive the stickers were perceived [34].…”
Section: Individual Characteristics and Evaluation Of Animal Stickerssupporting
confidence: 88%
“…For stickers of cartoon animals, cats were judged as cuter than other animals to express happiness 33 , and sadness 34 . Pigs and ducks were judged as less cuter than other animals to express agreement 35 , commitment 36 , grievance 37 , fun 38 .…”
Section: Cutenessmentioning
confidence: 99%
“…The keywords that appeared at least five times among target publications in the topic of psycholinguistics and pragmatic and usage-based language processing highlighted the following related themes [Language (17), Comprehension (11), Psycholinguistics (10), Speech (8), Speakers (7), Acquisition (6), Information (5), Context (5), and Perception (5)] and methodology [Eye-movements (5) and Children (5)]. In the topic of usage-based and pragmatic language learning, the keywords that occurred at least 10 times among target publications represented the themes highlighting Second Language Acquisition (76) and L2 Acquisition (15), Bilingualism (56), Language Acquisition (23), Spanish (20), Pragmatics (17), Study Abroad (15), Language, (14), Working Memory (14), Second Language (13), English (13), Vocabulary (13), Second Language Learning (12), German (10), Interlanguage Pragmatics (10), and fMRI (10).…”
Section: Bibliometric Analysismentioning
confidence: 99%
“…The co-occurrence and the bibliometric coupling analysis demonstrate that researchers are most interested in the processing of various interpersonal and socio-pragmatic functions in L1 and L2 speakers in the field of psycholinguistics, as well as factors underlying L2 acquisition from children to adults, and the impact of the cognitive and neurodevelopmental impairments in the field of second-language acquisition. One important direction is to combine the real-time neurophysiological recordings (such as eye-tracking, EEGs and fMRI) with the psycholinguistic paradigms for investigating the real-world language use to reveal the neurocognitive architecture underlying pragmatic language processing and those underlying language acquisition (e.g., [6,7] for some reviews). The use of virtual reality to create naturalistic scenarios will be a good complementary approach to test the impact of real-world social interaction on one's language processing and learning [8].…”
Section: Summary and Future Directionmentioning
confidence: 99%
“…One traditional view, which sees language processing as driven by domain-specific operations, argues that the language function is supported by the left perisylvian network, and early research on the language connectome mainly focused on the arcuate fasciculus that connects Broca’s and Wernicke’s Areas. However, recent work has shown that neural networks beyond language processing may support language and speech tasks in a broader and more communicative sense, proposing an insufficient role of traditional language networks underlying the language tasks and that domain-general networks, or neural networks serving other cognitive functions, such as executive and social functions, play crucial roles in certain language functions [ 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%